Role of Interface Chemistry in Opening New Radiative Pathways in InP/CdSe Giant Quantum Dots with Blinking‐Suppressed Two‐Color Emission. (24th June 2019) - Dennis, Allison M.; Buck, Matthew R.; Wang, Feng; Hartmann, Nicolai F.; Majumder, Somak; Casson, Joanna L.; Watt, John D.; Doorn, Stephen K.; Htoon, Han; Sykora, Milan; Hollingsworth, Jennifer A.
Abstract: InP/CdSe core/thick‐shell "giant" quantum dots (gQDs) that exhibit blinking‐suppressed two‐color excitonic emission have been synthesized and optically characterized. These type II heterostructures exhibit photoluminescence from both a charge‐separated, near‐infrared type II excitonic state, and a shell‐localized visible‐color excitonic state. Infrared emission is intrinsic to the type II QD, while visible emission can either be eliminated or enhanced through chemical modification of the InP surface prior to CdSe shell growth. Single‐QD photoluminescence measurements confirm that the dual color emission is from individual nanocrystals. The probability of observing dual emission from individual QDs and the extent of blinking suppression increases with shell thickness. Visible emission can be stabilized by the addition of a second shell of CdS, where the resulting InP/CdSe/CdS core/shell/shell nanocrystals afford the strongest blinking suppression, determined by analysis of the Mandel Q parameter. Transient absorption spectroscopy verifies that dual emission arises when hole relaxation from the shell to the core is impeded, possibly as a result of enhanced interfacial hole trapping at F − or O 2− defect sites. Electron–hole recombination in the shell then competes with slower type II recombination, providing a different mechanism for breaking Kasha's rule and allowing two colors of light to be emitted from one nanostructure. Abstract : Two‐color photoluminescence, both near‐infrared (NIR) and visible, is observed for type‐II InP/CdSe core/shell and InP/CdSe/CdS core/multishell nanocrystal quantum dots at the single particle level. Dual wavelength emission is elicited by chemical treatments to the InP core prior to shell growth, which introduces energetic barriers to hole migration. Multishell engineering gives rise to stable, blinking‐suppressed emission for both the NIR and visible range.